Classes are CANCELED! - Chabert, Jack (Chabert, Jack. Eerie Elementary, 2017)
Eerie Elementary seems to be falling down around the students and teachers, so Principal Winik decides the school must be torn down, but Sam, Lucy, and Antonio suspect that somehow this is all part of Orson Eerie's evil plan to live forever--and if it is they must find a way to prevent the demolition.